Sanksi Pidana Bagi Pelaku Perdagangan Satwa Liar yang dilindungi Secara Illegal - Nicholas Panggabean; Mella Ismelina Farma Rahayu (LPPM Universitas Ekasakti Padang, 2023)
Indonesia is a nation that is rich in natural resources, especially biological natural resources, both in the form of plants and animals in it. One of the crimes against wildlife that often occurs in Indonesia is the crime of illegal wildlife trade. Weaknesses in facilities and infrastructure as well as administrative weaknesses in the form of complicated bureaucracy can provide opportunities for parties carrying out wild animal trading activities. Legal protection for endangered animals and the environment is not without reason, because wild animals, like humans, are part of nature and also part of the environment or ecosystem. The law is a means that provides protection for all parties, including animals and the environment because the function of the law itself is to protect society and improve the welfare of society. In this research, the Normative Juridical research method is used, namely research that refers to the literature. Cases of crime against wildlife that still frequently occur today prove how weak the law enforcement of Law Number 5 of 1990 concerning Conservation of Natural Resources and Ecosystems is. Law enforcement against wildlife trade has not been carried out optimally because illegal wildlife trade still occurs.